2021
DOI: 10.5354/0719-0581.2021.55261
|View full text |Cite
|
Sign up to set email alerts
|

Inteligencia emocional y engagement en estudiantes de medicina: un estudio comparativo en tres países

Abstract: En este estudio se analiza la relación entre inteligencia emocional (IE) y el engagement académico en estudiantes de medicina. La inteligencia emocional se evalúa mediante la escala WLEIS y el engagement con la escala UWES-9 en una muestra de estudiantes de medicina (n = 522) pertenecientes a tres países: México (Universidad Nacional Autónoma de México, n = 127); Portugal (Universidad de Lisboa, n = 232) y España (Universidad de Extremadura, n = 163). Los análisis de regresión revelan que los estudiantes que t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
1
0
1
Order By: Relevance
“…In our study, emotional attention and repair also proved to be important skills in undergraduate Education students' perception of their own emotional competence. Similar results were obtained by Hernández-Vargas et al [46], who indicated that the higher the level of emotion recognition and management in university students, the higher their level of dedication in their initial training.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, emotional attention and repair also proved to be important skills in undergraduate Education students' perception of their own emotional competence. Similar results were obtained by Hernández-Vargas et al [46], who indicated that the higher the level of emotion recognition and management in university students, the higher their level of dedication in their initial training.…”
Section: Discussionsupporting
confidence: 88%
“…Third, the benefits obtained by healthcare professionals and students by intervening on EI and SOC, contribute to improve general well-being, commitment and motivation for a better performance in studies and clinical work ( 52 ). Consistent with the results, recent reviews highlight that EI and interventions on this variable have the benefit of improving productivity and clinical performance ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…La inteligencia emocional y la empatía son habilidades primordiales que todo personal del área de la salud, específicamente los médicos residentes, deberían poseer porque estas no solo tienen beneficios para el paciente, sino para ellos mismos, ya que se ha demostrado que, ante niveles altos de inteligencia emocional, existe menos cansancio emocional y síntomas psicosomáticos en los médicos. En los pacientes, el apego a su tratamiento y el nivel de satisfacción con respecto a la atención recibida es mayor 6 .…”
Section: Abstract: Emotional Intelligence; Empathy; Medical Residentunclassified